Vertical gardening and Syrian women refugees in Lebanon: an exploratory study on motivation for gardening and depression relief. Issue 10 (3rd October 2021) - Talhouk, S. N.; Chalak, A.; Kamareddine, Z.; Fabian, M.; Itani, M.; Ferguson, N.
ABSTRACT: Refugees and the displaced experience challenges which can lead to mental health illnesses, including depression. In this study, the effectiveness of gardening in reducing depression and improving the lives of displaced Syrian women in Lebanon was explored. Considering that the displaced had limited outdoor space and no access to land, vertical gardening units were used. Forty-four participants residing in four displaced communities in North Lebanon joined the 6-months gardening programme, which was designed as a quasi-experimental exploratory study. Data on depression scores were collected at the preparatory phase and at 24 weeks post-intervention using the Beck Depression Inventory (BDI-II) and analysed using a paired t-test. Results revealed that participants were less depressed at the end of the gardening programme, with depression scores significantly lower than preparatory phase scores. Group interviews were also conducted to assess women's perception of gardening halfway through the intervention phase. Women's engagement in gardening activities was also reflected by estimating yields. Participants indicated that they joined the programme because they saw it as a stress relief activity, they were interested to learn about vertical gardening, they enjoyed the aesthetic value of plants, they wanted to produce food and they felt that gardening provided an opportunity to socialise. Our findings suggest that aid organisations may consider vertical gardening as a therapeutic and social activity in situations where displaced women are confined to limited open spaces.